If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3a + 9) = 0 Reorder the terms: 3(9 + 3a) = 0 (9 * 3 + 3a * 3) = 0 (27 + 9a) = 0 Solving 27 + 9a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 9a = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 9a = 0 + -27 9a = 0 + -27 Combine like terms: 0 + -27 = -27 9a = -27 Divide each side by '9'. a = -3 Simplifying a = -3
| 9x-.2y=4 | | -7x-6-7x=-118 | | 14-.5y=x | | 4/100=x/(4178.891+x) | | 5x^2-75x+50=0 | | −7/8−1/2s=−1/4 | | -3y+27=-15x | | 10-2*7+4= | | 5x3/2+(-9/4) | | 1/6|1/3(x-2/5)|=5/6(x+1/4) | | −7/8−1/2s=-14 | | 1/6[1/3(x-2/5)]=5/6(x+1/4) | | 9a^2+11x+4=0 | | 1/3x+1/4x=3/4x+1/3 | | 4p-5+2p=-17 | | -24=-9q+3 | | 0=t^2-6t-7 | | 7n+7=28 | | 1/2a+1/3a=-15 | | x/7=x/8-9 | | 1/2a+1/3a=2−17 | | 22x-2y=46 | | 5t^2+15t=-10 | | 15y^3-24y^2-12y=0 | | 5x-10y-100=0 | | 16x-4x=-6-5 | | x+y=2y-20 | | 16x-4x=-4-6 | | 8x^2-30b+18=0 | | x+50=3x-10 | | y=-x^2+120x+4000 | | 10x-3y-81=0 |